Legal Certainty Dualism of Civilian Positions Active Members of the Indonesian Police - Rais Firdaus Handoko; Widhi Handoko (Unissula, 2026)
This study aims to analyze the legal status of active police officers following the Constitutional Court's ruling to formulate a direction for legal harmonization consistent with the principle of legal certainty. This study uses a normative juridical method. The results indicate that the removal of the phrase